Customized Moodle-Based LMS for Arabic Grammar: Transforming Al-Qawa'id Al-Naḥwiyah Pedagogy in Higher Education - Ainun Syarifah; Muchammad Nur Huda; Muhamad Omar Fuad Hasim (Ijaz Arabi Journal of Arabic Learning, 2026)
This study aims to develop and examine the effectiveness of a customized Moodle-based Learning Management System (LMS), namely “Moodlenesia”, for teaching Al-Qawā'id Al-Naḥwiyah in higher education. The research employed a research and development approach using the ADDIE model combined with a quasi-experimental design to evaluate the impact of the LMS on students’ learning outcomes. The participants consisted of 80 students divided into experimental and control groups. Data were collected through learning achievement tests, student response questionnaires, and expert validation of instructional media and content. The findings indicate that Moodlenesia demonstrates a high level of feasibility based on expert evaluations and significantly improves students’ learning outcomes compared with conventional instruction. The integration of interactive features, instant feedback, and flexible learning access contributed substantially to students’ understanding of Arabic grammatical concepts. This study highlights the potential of customized LMS platforms to transform Arabic grammar pedagogy into a more interactive and adaptive learning environment in higher education.